Going it alone - Willig, George; Bergman, Drew (Garden City, N.Y. : Doubleday, 1979)
Autobiography of the "human fly" who climbed the sheer wall of the World Trade Center in New York City, covering his life before and after the climb and describing the hours he spent on the wall
Keywords: Willig, George; World Trade Center (New York, N.Y.); Mountaineers -- United States -- Biography